Faktor-Faktor yang Berhubungan dengan Kepuasan Pasien di Instalasi Gawat Darurat - Ameliati, Sri; Putri, Yana Maysah (Pustaka Galeri Mandiri, 2025)
Patient satisfaction is one of the determining factors for the success of a health service. Responsive staff, adequate service quality, standardized waiting time in the Emergency Department (ED), patient comfort and facilities, as well as professional medical personnel who are always available 24 hours a day, are essential aspects of emergency care. This study aims to determine the factors associated with patient satisfaction in the Emergency Department. This research employed a quantitative method with a descriptive-analytic design using a cross-sectional approach. The study was conducted in the Emergency Department of Prof. H. Muhammad Yamin, SH Regional General Hospital from March to 13, 2025, with a total sample of 73 respondents. Sampling was carried out using the probability sampling technique. Data were analyzed using univariate and bivariate analyses with the Chi-Square test, and the level of significance was set at p < 0.05. The results showed that 55 respondents (75.3%) rated the quality of service as “Good”; 53 respondents (74.0%) stated that the waiting time met the standard; 57 respondents (78.1%) rated the facilities provided as “Good”; and 52 respondents (71.2%) expressed satisfaction with the overall quality of service. There was a significant relationship between service quality, waiting time, and facilities with patient satisfaction in the Emergency Department. It is expected that patients will improve their understanding of their rights as healthcare recipients, including the right to obtain high-quality, safe, and standardized health services